If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + -12 = 0 Reorder the terms: -12 + 3w = 0 Solving -12 + 3w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3w = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 3w = 0 + 12 3w = 0 + 12 Combine like terms: 0 + 12 = 12 3w = 12 Divide each side by '3'. w = 4 Simplifying w = 4
| 4/3d^2+5 | | -6+n/2-10 | | y=2(x-3)(x-2) | | -38-8p=-6(1+2p) | | (4x^2-2)+3x+1=0 | | 1/2y+6=-17 | | (y-5)-(y+5)=2y | | (X/5)(2)=1 | | 2(5c-1)-14=8c+2 | | -10a-3a= | | -8x+25=-7 | | 2t^3-10t^2-48t=0 | | 11h-h-9h=-16 | | 9+8b+6-5=1-b | | 174t+4=8 | | 5n-6=49 | | x+2/3=5/7 | | 8x-(4x-5)=37 | | kn=-4f+9v | | 5-4x=11+2x | | -1-2x=1-3x | | 175.000+550*1x=35000+168000x | | z^3-49z=0 | | 31/2*41/2 | | 5v^2-10v=0 | | -12=2(n+3) | | 2x-14.5=0.5x+50 | | 3n=1-m | | 9-5(4-3)=16m/3 | | 7s+4(3-5)=18 | | y-x=1/3(x+14) | | 1/4(8x+4)-17=-1/2(4x-8) |